A New Self-Report Quality of Life Questionnaire for Children With Neuromuscular Disorders: Presentation of the Instrument, Rationale for Its Development, and Some Preliminary Results. (February 2014) - Orcesi, Simona; Ariaudo, Giada; Mercuri, Eugenio; Beghi, Ettore; Rezzani, Cristiana; Balottin, Umberto
Improvement of quality of life in neuromuscular disorders is a primary objective, both in management of affected children and in the context of therapeutic trials. Quality of life is a subjective concept and it is crucial to gather information directly from patients. We created the SOLE Questionnaire for NMDs, a new instrument designed to investigate quality of life in children with neuromuscular disorders, and tested it in a study population of 78 patients and in 81 healthy children aged 5 to 13 years. The SOLE Questionnaire, characterized by a visual and neutral approach, was well received, practical, rapid to administer, and able to discriminate between patients and controls. We also confirmed the presence of disagreement about children's quality of life between children and their parents. We suggest that our new approach could help to improve understanding of quality of life in children with neuromuscular disorders.